Keputusan Nasabah KUR Dilihat dari Suku Bunga dan Kualitas Pelayanan Pada Bank Mandiri Cabang Imam Bonjol Kota Padang - Doni Marlius (JURNAL PUNDI, 2020)
The purpose of this study was to analyze the effect of interest rates and service quality partially and simultaneously on customer decisions using KUR credit at the Bank Mandiri Imam Bonjol Branch of Padang City. The research method used is descriptive quantitative. The sampling technique used is non-probability sampling method with accidental sampling so that from the population a sample of 100 respondents was taken, the data collection method used was observation, questionnaire and literature review. From the t-test, the interest rate has a positive and significant influence on the decision to use credit KUR at Bank Mandiri Imam Bonjol, Padang City, tangible has no effect on the decision to use credit KUR at Bank Mandiri Imam Bonjol, Padang City, reliability has a positive and significant influence on the decision using KUR credit at Bank Mandiri Imam Bonjol of Padang City, responsiveness (X4) negatively and significantly affected the decision to use credit for credit at Bank Mandiri Imam Bonjol in Padang City, assurance had a positive and significant influence on the decision to use credit curses at Bank Mandiri Imam Bonjol Kota Padang and empaty did not affect the decision to use credit for credit at Bank Mandiri Imam Bonjol, Padang City. From the results of the F test, it is proved that the interest rate and service quality variables simultaneously have a significant and positive effect on the decision to use credit curses at Bank Mandiri Imam Bonjol, Padang City.